The emergence of a dipole-like mode in Arctic atmospheric circulation conducive to European heat waves - Doo Young Lee; Sang-Wook Yeh; Yong-Han Lee; Wenju Cai; Guojian Wang; Young-Min Yang (Communications Earth & Environment)
Abstract Since the 2000s, there has been a marked acceleration in the decline of summer Arctic sea ice, accompanied by an increase in Arctic sea ice variability. However, the impact of Arctic sea ice decline on changes in Arctic atmospheric circulation and its implications for mid-latitude summers remain unclear. Here we propose that the emergence of a dipole-like mode of Arctic atmospheric circulation, driven by the Arctic sea ice decline, is linked to the intensification of temperature rise and increased European heat waves. Idealized model experiments support that the recent intensification of the Arctic sea ice decline is a key driver for the emergence of dipole-like atmospheric circulation in mid-latitude summer. The accelerated Arctic sea ice decline weakens the meridional temperature gradient and the zonal wind in Eastern Europe, develops an anti-cyclonic circulation, and contributes to the intensification of European heat waves.